Effects of balance and kinematic factors on archery score during archery shooting - An, H.-S. (Journal of the Korea Convergence Society, 2018)
In this study, we analyzed the balance of the both legs and the kinematic analysis of the upper limb segments and joints during archery shooting and compared the differences according to the scores. 9 K-university elite archery athletes participated. Each archer was asked to shoot 3-shots and 5-ends on a 122 cm target at a distance of 70 m. Seven infrared cameras (Qualisys, sweden) and two force plates (Kistler, Switerland) were used to calculate the upper limb segments and joint movements and the center of pressure (COP). When the archers shot 8 points, range of motion of elbow joint angle on drawing-arm and mediolateral COP range of motion on the left foot were larger than when 9-10 points were shot (p<.05). In order to maintain a high score in the archery game, constant balance is required, and the balance of the left foot supporting the bow during the shooting is an important factor. In addition, minimizing elbow joint movement of the drawing-arm supporting the bow will help stabilized shooting.